Hakikat Fitrah Manusia dan Pendidikan Anak dalam Pandangan Islam (Suatu Tinjauan Teoritis) - Oktori, Agus Riyan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
: Children's education should be based on what is called human nature, because every child who is born has a natural disposition. The environment that exists in educational institutions and the community around the place of residence has a very important role in the effort to develop this nature. Education based on the concept of humanizing humans should be able to develop this potential or nature. In this paper, we will try to examine the nature of human nature and how to educate children when referring to the Islamic view by using library research or library research. The common thread in this paper is that each student has quite a variety of potential, this potential should have a place or container so that it can be maximized. The development of this potential is none other than through a process called education. Education should not always ground students who have only cognitive abilities, there are many special things related to the potential of students who can be developed through the educational process.